The Use of Malay Language in Pekanbaru: An Ethnographic Research - Herlinda (Center of Language and Cultural Studies [CLCS], 2022)
This study aims to determine the use of the Malay language in the capital city of Riau Province, Pekanbaru. The problem of the study is to find out the factors that influence the use of the Malay language from positive and negative aspects according to the culture of the community. This study consults 5 informants: traditional leaders, youth leaders, intellectual figures, Pekanbaru City Government, and Riau Traditional Institutions in Pekanbaru City. This research uses a triangulation method to explain that facts cannot be checked with a degree of confidence with one or more theories. For this reason, the best step to take is to look for comparative explanations by parsing the pattern of relationships and including explanations that emerge from the analysis to find comparison themes based on the possibility of available data. The results of the analysis show that there is still a lack of awareness of the people of Riau to maintain the Malay language in the city of Pekanbaru because of the low sensitivity to cultural preservation, especially regional/local languages.